Reversible hydrogen storage in LiBH4-MH2 (M = Ce, Ca) composites - Jin, Seon-Ah; Lee, Young-Su; Shim, Jae-Hyeok; Cho, Young Whan (AMER CHEMICAL SOC, 2008)
Hydrogen desorption and absorption properties of two destabilized systems, 6LiBH(4) + CeH2 + 0.2TiCl(3) (Ce system) and 6LiBH(4) + CaH2 + 0.2TiCl(3) (Ca system), have been characterized. The theoretical hydrogen capacity is 7.39 and 11.67 wt % for the Ce and Ca systems, respectively. Both systems follow the thermodynamically predicted dehydrogenation reaction path, forming LiH and metal hexaborides (MB6) as the dehydrogenated products, which is confirmed by X-ray diffraction data. After hydrogenation at 623 K (Ce system) or 673 K (Ca system) under 100 bar H,, pressure for 20 h, LiH + MB6 was converted back to the initial reactants, LiBH4 + MH2. The amount of H-2 released during the first and the second dehydrogenation proves that the first dehydrogenation-hydrogenation cycle is fully reversible. The temperature required to achieve the reversibility is lower in the case of the Ce system, in agreement with our thermodynamic calculation. Our study is the first report of reversible hydrogen storage in 6LiBH(4) + CeH2; this composite is one of the few destabilized systems shown to be fully reversible at this relatively low temperature range with a reasonably high hydrogen capacity.
Keywords: MODIFIED LITHIUM BOROHYDRIDES; HYDRIDE; DESTABILIZATION; DIFFRACTION; MGH2